The cost accounting at universities in Spain: ananalysis in structure of the syllabus of the subjects at graduation (Revista Brasileira de Contabilidade e Gestão, 2016)
Aiming to identify the profile of Cost Accounting subjects in graduation courses offered at Spanish universities, this essay has the objective to verify the syllabus of the subject which approach the cost accounting content in the graduation courses of Accounting and Finance, with the objective of identity its basic structure, objectives, methodologies, evaluation process, content, bibliographies. This essay is descriptive, with qualitative and quantitative approach. As for the technical proceedings, the strategy of the research is documental. The used technique for the data collection was analysis of secondary data, based on the syllabus with the content of Cost Accounting of Spanish universities. For the problem approach it was used qualitative and quantitative methodologies. In general, the results showed that: (i) the cost and management subject has 6 credits; (ii) the content of the subject deal with: Conceptos Básicos/Fundamentales de Costes, followed by Costes por Procesos, Costes Estándares, Los Centros de Costes/Centros o areas de Responsabilidad, Los Sistemas de Costes Basadosenlas Actividades ABC), El Coste Completo o de Absorción e Asignación de Costes. Also topics such as: Presupuestos, Costes Variables y Costes Fijos Costes Directos y Costes Indirectos and El Análisis Coste-Volumen- Beneficio (CBV); (iii) students are evaluated with a final test, partial test, individual jobs, exercises and group work; (iv) the references used are from main authors such as: Horngren, Forster and Datar, and his job named Contabilidad de Costes. It is observed a certain homogeneity regarding the structure of the syllabus among the researched universities.
Keywords: cost accounting; syllabus; Spanish universities